SARS-CoV-2 seroprevalence in healthcare workers of a Swiss tertiary care centre at the end of the first wave: a cross-sectional study. Issue 7 (5th July 2021) - Meylan, Sylvain; Dafni, Urania; Lamoth, Frederic; Tsourti, Zoi; Lobritz, Michael A; Regina, Jean; Bressin, Philippe; Senn, Laurence; Grandbastien, Bruno; Andre, Cyril; Fenwick, Craig; D'Acremont, Valerie; et al.
Abstract : Objective: To assess the SARS-CoV-2 transmission in healthcare workers (HCWs) using seroprevalence as a surrogate marker of infection in our tertiary care centre according to exposure. Design: Seroprevalence cross-sectional study. Setting: Single centre at the end of the first COVID-19 wave in Lausanne, Switzerland. Participants: 1874 of 4074 responders randomly selected (46% response rate), stratified by work category among the 13 474 (13.9%) HCWs. Main outcome measures: Evaluation of SARS-CoV-2 serostatus paired with a questionnaire of SARS-CoV-2 acquisition risk factors internal and external to the workplace. Results: The overall SARS-CoV-2 seroprevalence rate among HCWs was 10.0% (95% CI 8.7% to 11.5%). HCWs with daily patient contact did not experience increased rates of seropositivity relative to those without (10.3% vs 9.6%, respectively, p=0.64). HCWs with direct contact with patients with COVID-19 or working in COVID-19 units did not experience increased seropositivity rates relative to their counterparts (10.4% vs 9.8%, p=0.69 and 10.6% vs 9.9%, p=0.69, respectively). However, specific locations of contact with patients irrespective of COVID-19 status—in patient rooms or reception areas—did correlate with increased rates of seropositivity (11.9% vs 7.5%, p=0.019 and 14.3% vs 9.2%, p=0.025, respectively). In contrast, HCWs with a suspected or proven SARS-CoV-2-infected household contact had significantly higher seropositivity rates than those without such contacts (19.0% vs 8.7%, p<0.001 and 42.1% vs 9.4%, p<0.001, respectively). Finally, consistent use of a mask on public transportation correlated with decreased seroprevalence (5.3% for mask users vs 11.2% for intermittent or no mask use, p=0.030). Conclusions: The overall seroprevalence was 10% without significant differences in seroprevalence between HCWs exposed to patients with COVID-19 and HCWs not exposed. This suggests that, once fully in place, protective measures limited SARS-CoV-2 occupational acquisition within the hospital environment. SARS-CoV-2 seroconversion among HCWs was associated primarily with community risk factors, particularly household transmission.